En krig i det fjerne. Børne- og ungdomslitteratur om krigen i Afghanistan (2001-) - Skyggebjerg, Anna Karlskov (Passage - Tidsskrift for litteratur og kritik, 2016)
“A War in the Distance. Children’s and Young Adult’s Literature about the War in Afghanistan (2001-)” In the last decade several Danish children’s books about the war in Afghanistan and other ongoing military conflicts have been published. These books belong to various genres from novels to non-fiction picture books, and they have several purposes; from entertainment to classroom reading. They depict war in many ways and they address child readers at different levels. What they have in common is an ambition of realism and sharing of knowledge (or education) about war. The key questions in this article are: how is war constructed and how is the child reader confronted with extreme situations and the crucial consequences of war? The theoretical background for this article is research in descriptions of war in children’s literature and literature in general, theory about the construction of childhood in children’s literature and genre theory focused on the relation between fiction and non-fiction in children’s literature.